A Postcolonial Reading of Tacitus' Agricola - Cui, Haojiong (International Journal of Social Sciences and Public Administration, 2026)
This study aims to re-examine the narrative of Roman imperialism and its constructed cultural hierarchy within Tacitus's Agricola through a postcolonial lens. Despite being composed in the early second century AD, the patterns of domination, assimilation, and resistance revealed in Agricola resonate profoundly with modern colonial dynamics. By dissecting Tacitus's portrayal of Roman expansion in Britain, this study demonstrates how the empire packaged conquest as a civilising mission while simultaneously relying on violence, cultural obliteration, and ideological legitimisation. Caligula's famous indictment-‘They create desolation and call it peace’-serves as the central argument, exposing the inherent contradictions within imperial discourse. Employing modern postcolonial concepts-alterity, hegemonic discourse, and cultural conquest-this paper demonstrates how Tacitus both participated in and subtly critiqued Roman imperial ideology. Concurrently, this study emphasises a fundamental divergence between Tacitus's moral concerns and modern postcolonial theory: the former primarily reflects on internal Roman corruption, while the latter examines the structural oppression endured by colonised peoples. Through this comparative lens, the essay reveals the intricate interplay of power, culture, and identity within the Agrippina, elucidating both the value and limitations of applying postcolonial theory to the context of ancient empires.